Worse Self-Reported Hearing Ability Is Associated With Greater Perceived Physical and Mental Fatigability. (17th December 2021) - Gmelin, Theresa; Moored, Kyle; Lin, Frank; Golub, Justin; Wojczynski, Mary; Boudreau, Robert; Galvin, Angeline; Glynn, Nancy W
Abstract: Older adults with hearing loss often report higher fatigue due to effortful listening. We evaluated whether self-reported hearing ability is associated with perceived physical and mental fatigability (a more sensitive measure than fatigue) using the Pittsburgh Fatigability Scale (PFS). Older adults (N=2, 558) from the Long Life Family Study Visit 2 (71.5±11.4 years; 54.8% women) completed PFS and self-reported hearing ability (worse=[fair, poor, very poor, deaf] or better=[good, excellent]). Age-adjusted PFS Physical and Mental scores were 2.3 and 2.5 lower, respectively, for worse vs. better hearing (p<.0001). Generalized estimating equations adjusted for family-relatedness, site, age, sex, cognitive function (Mini-Mental State Examination), education, and self-reported health. Compared to individuals with better hearing, those with worse hearing had a 42% and 44% greater odds of physical (≥15) (CI:1.12-1.80, p=0.0042) and mental(≥13) (CI:1.13-1.84, p=0.0034) fatigability, respectively. These observed associations may potentially be explained via complex psychosocial and cognitive aging pathways (e.g. effortful listening) to be examined in future work.